The Immunotherapy of Canine Osteosarcoma: A Historical and Systematic Review. (30th April 2015) - Wycislo, K.L.; Fan, T.M.
<x xml:space="preserve">Abstract</x> Osteosarcoma is a malignant mesenchymal neoplasm that accounts for the majority of primary bone tumors in dogs and shares biological and clinical similarities with osteosarcoma in humans. Despite dose intensification with conventional cytotoxic therapies, survival times for dogs and humans diagnosed with high‐grade osteosarcoma have not changed in the past 20 years, with the principal cause of mortality being the development of pulmonary metastases. Given the therapeutic plateau reached for delaying metastatic progression with cytotoxic agents, exploration of alterative adjuvant therapies for improving management of osteosarcoma micrometastases is clinically justified. Evidence suggests that osteosarcoma is an immunogenic tumor, and development of immunotherapies for the treatment of microscopic lung metastases might improve long‐term outcomes. In this review, the history and foundational knowledge of immune interactions to canine osteosarcoma are highlighted. In parallel, immunotherapeutic strategies that have been explored for the treatment of canine osteosarcoma are summarized. With a greater understanding and awareness for how the immune system might be redirected toward combating osteosarcoma metastases, the rational development of diverse immune strategies for managing osteosarcoma holds substantial promise for transforming the therapeutic landscape and improving disease management in both dogs and human beings.